Impact Analysis of Government Fertilizer Subsidy Policy on Cocoa Farm Productivity and Income in East Kolaka Regency - Kah Inang Fitrah Ramadhan; Marsuki Iswandi; Agustono Slamet (International journal of technology and education research, 2025)
This study aims to analyze the impact of the government's fertilizer subsidy policy on the productivity and income of cocoa farming businesses in East Kolaka Regency which was carried out from June 2024 to July 2024. This study uses primary and secondary data, and the data is analyzed using the t-test assisted by SPSS software. The variables in this study include fixed costs (equipment depreciation costs and land taxes), variable costs (seedling, fertilizer, pesticide and labor purchase costs), revenue, and income. The results showed that there was no significant difference in productivity, while there was a significant difference in income. Where the average productivity of farmers using fertilizer subsidies was 722 Kg/Ha while non-fertilizer subsidized farmers were 712 Kg/Ha. The average income generated by fertilizer subsidized farmers was IDR 33,814,583/Year while the average income of non-fertilizer subsidized farmers was IDR 25,470,167/Year. The impact of fertilizer subsidies on cocoa farming has a positive impact on farmers' income, this is because there is a significant difference, while there is no significant impact on productivity